Efeito da natação no perfil lipídico e na hipertrofia ventricular esquerda de camundongos hiperlipidêmicos - Terra, Gerusa Dias Siqueira Vilela (2010)
Regular physical activity combined with healthy eating habits are important factors in primary prevention and therapeutic support in cardiovascular diseases, such as dyslipidemia and left ventricular hypertrophy, which are outstanding risk indicators of cardiovascular morbidity and mortality. This study assessed the effects of swimming on the lipid profile and left ventricular structures in hyperlipidemic mice. Twenty-eight male LDLr-/- mice were randomly separated into 4 groups: sedentary, fed a standard diet (S); exercising, fed a standard diet (E+Nat); sedentary, fed a hyperlipidic diet (S+HL); and exercising, fed a hyperlipidic diet (E+HL). The exercising mice swam daily for 60 minutes during 60 days. Blood was collected for measuring the plasma levels of triglycerides, total cholesterol and its fractions (LDL, HDL, VLDL). The heart was removed and the left ventricle was weighed fresh to calculate the ratio left-ventricle weight (mg)/body weight (g). The results showed that swimming was more effective in improving lipid plasma levels when combined with a balanced diet, thereby confirming that it is essential to associate physical exercise and diet. Swimming resulted in eccentric left ventricular hypertrophy in the standard-diet group and decreased interstitial collagen deposition in the myocardium of the high-fat-diet animals, which may indicate an improved diastolic function with consequent improvement in the systolic function. It was concluded that regular aerobic exercise induce cardiac adaptations that improve whole body physiology by promoting health and preventing diseases. However, it is extremely important to note that exercise should be regular and associated with an adequate diet.